К познанию веснянок сем. Nemouridae (Plecoptera) Сахалина и Курильских островов - Жильцова, Л.А. (Вестник зоологии, 1979)
At present 29 species of stoneflies are known in Sakhalin, 13 species in Kunashir.
Four species more are mentioned in the paper, one of them, Amphinemura dentifera sp. n., being new for science and two species, A. decemseta Oka m., being new for the USSR fauna. The widely distributed palearctic species A. standjussi Ris. is mentioned for Sakhalin.